Attitudes and perceptions of university students towards calculus / Tang Howe Eng, Nor Hazizah Julaihi and Voon Li Li - Tang, Howe Eng; Julaihi, Nor Hazizah; Voon, Li Li (Research Management Institute (RMI), 2013)
This study seeks to examine university students’ attitudes and their perceptions on calculus education. Lecturers’ suggestions to remedy the current situation of calculus learning were also investigated. The instruments of this study consisted of three sets of questionnaires, aimed at collecting data regarding students’ attitudes and perceptions on calculus and lecturers’ suggestions. The respondents consisted of 278 full-time diploma students in a public university in Malaysia. The findings indicate that the students’ attitudes towards the Course of calculus according to gender were insignificant. However, there was a significant difference in the students’ attitudes towards the Field of calculus between female and male students. Students of Pre-Calculus and Calculus I were found to be feeling, thinking, and behaving similarly about calculus. Their attitudes towards the Field of calculus among the four engineering and science programmes were significant. After attempting 39.27% of the given questions, students’ perceptions on the difficulty of the questions remained the same, which was neither easier nor harder than they expected. Nevertheless, students’ perceptions changed positively (questions more difficult than expected) in 19.45% of the questions and negatively (questions easier than expected) in 41.28% of the questions. The implications from these findings provided inputs to improve calculus teaching and learning. Information regarding students’ attitudes toward calculus could help lecturers to design comprehensive calculus lessons that suit all kinds of students. Students also need to change their attitudes towards calculus, for example by having a closer inspection of the exact nature of the calculus questions before attempting them.